Gold(I)-Catalyzed Domino Cyclization for the Synthesis of Tricyclic Chromones - Li, Zhiqiang; Li, Qingjiang; Liu, Guo-Kai; Chen, Weimin; Peng, Xiao-Shui; Wong, Henry N. C. (Synlett, 2015)
A simple and efficient method for the synthesis of tricyclic chromones has been developed. In this approach, tricyclic chromones were synthesized from a diverse range of phenols and alkynes through a Sonogashira coupling and subsequent gold-catalyzed intramolecular domino cyclization.
Keywords: chromone; gold-catalyzed; intramolecular cyclization; domino; Brønsted acid